A comparative surface analysis of zirconia, titanium and titanium-zirconium dental implants - Miranda, Mónica (2015)
INTRODUCTION: the osseointegration of the implant depends upon the surface itself. In addition to the biofunctional aspects, aesthetic considerations began to gain relevance, and thus came the ceramic implants (eg zirconia) as an alternative to titanium implants. PURPOSE: characterize the surface of titanium implants, titanium- zirconium and zirconia, investigating the relationship between characteristics such as chemical composition and crystallographic, wettability and roughness in the known results of osseointegration. MATERIALS AND METHODS: a Straumann Standard Plus SLA® implant tissue level of titanium, two implants Straumann SLA® Roxolid® Loxim™ titanium and zirconium (a bone level and a tissue level), two Straumann zirconia implants Pure Ceramic ZLA™. The tests are: X-ray diffraction; optical profilometry; measurement of contact angle; scanning electron microscopy with energy dispersive X-ray spectrometry and artificial aging. RESULTS: In the X-ray diffraction analysis all implants have confirmed the existence of the base elements; the zirconia implant obtained lower roughness values on the rough area; the monoclinic fraction of zirconium oxide was superior to the tetragonal fraction before and after artificial aging; the zirconia implant on scanning electron microscopy showed fine and rounded grains. CONCLUSION: Association between the topographical micrometer aspect with the nanometer one; it was found that the roughness of the zirconia implant is lower than the titanium and the titanium-zirconium implants, the last one have larger surface roughness values; after aging, it was found that the proportion of zirconium oxide in the monoclinic phase increased and remained above the proportion of tetragonal phase.